Innovative Strategies for End-of-Life Optimization in Renewable Energy - Abdelsattar, Ahmed Adel Abdelaal (AUC Knowledge Fountain, 2026)
This thesis investigates the governance of solar photovoltaic (PV) end-of-life (EoL) management in Egypt- a country experiencing rapid renewable energy expansion alongside deeply rooted informal systems. It identifies a Growth-Governance Paradox: while solar PV capacity is increasing rapidly in line with Egypt’s ambitious energy and development agendas, the institutional, financial, and stakeholder arrangements required to manage the resulting PV waste remain underdeveloped. This creates a critical governance gap between the country’s energy and waste regimes. The research argues that prevailing frameworks such as circular economy (CE) and extended producer responsibility (EPR) are predominantly designed for formal, high-enforcement contexts. Consequently, they fail to account for hybrid settings like Egypt, where policy infrastructures are still emerging and where intermediaries, market enablers, and informal actors play pivotal roles. To address this gap, the study employs a pragmatist, abductive, embedded case study design. It integrates policy and legislative analysis, comparative learning from international PV EoL governance models (Learning Units), and qualitative semi-structured interviews with experts representing Egypt’s formal, market-based, and informal subsystems. Drawing on these insights, the thesis develops and applies the CYCLE-PV Integrated Governance Framework, which organizes PV EoL governance around five diagnostic dimensions: Compliance, Yield, Coalitions, Lifecycle, and Equity. Using this framework to contrast international “expected” patterns with Egypt’s “actual” arrangements reveals critical shortcomings in regulatory clarity, value capture, cross-sector coordination, planning for early-loss modules, and inclusive participation of academia, informal actors, and enablers such as social entrepreneurs and civil society organizations. The study contributes empirically by offering one of the first comprehensive mappings of Egypt’s emerging PV EoL landscape. Practically, it introduces a governance diagnostic strategy and sandbox roadmap that outlines phased, hybrid approaches to integrate diverse stakeholders. These strategies aim to proactively manage the impending wave of PV waste and capitalize on the present “golden window” for reform before structural lock-ins occur.